Direct Electrochemical Preparation of Cobalt, Tungsten, and Tungsten Carbide from Cemented Carbide Scrap - Xiao, Xiangjun; Xi, Xiaoli; Nie, Zuoren; Zhang, Liwen; Ma, Liwen (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2017)
A novel process of preparing cobalt, tungsten, and tungsten carbide powders from cemented carbide scrap by molten salt electrolysis has been investigated in this paper. In this experiment, WC-6Co and NaCl–KCl salt were used as sacrificial anode and electrolyte, respectively. The dissolution potential of cobalt and WC was determined by linear sweep voltammetry to be 0 and 0.6 V ( vs Ag/AgCl), respectively. Furthermore, the electrochemical behavior of cobalt and tungsten ions was investigated by a variety of electrochemical techniques. Results of cyclic voltammetry (CV) and square-wave voltammetry show that the cobalt and tungsten ions existed as Co 2+ and W 2+ on melts, respectively. The effect of applied voltage, electrolysis current, and electrolysis times on the composition of the product was studied. Results showed that pure cobalt powder can be obtained when the electrolysis potential is lower than 0.6 V or during low current and short times. Double-cathode and two-stage electrolysis was utilized for the preparation of cobalt, tungsten carbide, and tungsten powders. Additionally, X-ray diffraction results confirm that the product collected at cathodes 1 and 2 is pure Co and WC, respectively. Pure tungsten powder was obtained after electrolysis of the second part. Scanning electron microscope results show that the diameters of tungsten, tungsten carbide, and cobalt powder are smaller than 100, 200, and 200 nm, respectively.